Kemampuan Sosial Anak Usia Dini: Sebuah Tinjauan Etnoparenting pada Lembaga Pendidikan Anak Usia Dini - Fitroh, Siti Fadjryana; Latif, Muhammad Abdul; Yuandana, Tarich; Trisetiawati, Jelita; Aprilia, Winda Dwi (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to explore the role of Madurese ethnoparenting in shaping young children's social skills. By highlighting core values such as solidarity, cooperation, independence, and politeness, it examines how culturally rooted parenting practices contribute to early social development and their integration into early childhood education.Method – This study employs a qualitative case study approach conducted at TK Muslimat NU Darunnajah Kamal, Bangkalan. Data sources include relevant literature and field data from teachers and parents. Data collection involves in-depth interviews with parents, teachers, and school management, followed by data reduction, presentation, and conclusion drawing.Findings – The study found that Madurese parenting culture plays a significant role in shaping the social skills of young children. Values inherent in Madurese culture, such as solidarity, cooperation, independence, sociability, friendliness, and good manners, provide a strong foundation for children to learn positive social interactions. Furthermore, integrating Madurese parenting culture into early childhood education practices can create an environment that optimally supports children's social development. This culture helps children understand the importance of positive social relationships while nurturing a sense of responsibility, empathy, and collaboration. Research Implications – This study contributes to the theoretical understanding of ethnoparenting by demonstrating its practical application in early childhood education. The findings offer valuable insights for policymakers and educators on integrating local cultural values into curricula, thereby creating more inclusive and effective educational models.